Матрица функций института собственности - Горчакова, Е.Н. (Культура народов Причерноморья, 2013)
В работе предлагается трехмерная матрица функций института собственности,
которая релевантно систематизирует три класса факторов и используется для многостороннего
исследования содержания и формы отношений собственников к собственности. Разработанная
матрица отличается иерархичностью и строгой упорядоченностью факторов, которые влияют на
состояние института собственности. Это класс факторов субъектов собственности (частник,
группа, общество); класс объектов собственности (ресурсы, средства, блага) и класс отношений
субъекта к объекту (присвоение, владение, отчуждение). У роботі пропонується тривимірна матриця функцій інституту власності, яка релевантно
систематизує три класи факторів і використовується для багатостороннього дослідження змісту і
форми відносин власників до власності. Розроблена матриця відрізняється ієрархічністю і
впорядкованістю факторів, які впливають на стан інституту власності. Це клас факторів суб'єктів
власності (приватник, група, суспільство); клас об'єктів власності (ресурси, кошти, блага) і клас
відносин суб'єкта до об'єкта (привласнення, володіння, відчуження). The article proposes a three-dimensional function matrix of ownership institute, which relevantly
organizes three classes of factors and is used to study the content and forms of owners’ attitude to the property.
The developed matrix comprises the hierarchical factors that affect the state of the ownership institute. These are
the class of ownership subjects (a private owner, a group, society), the class of property objects (resources,
facilities, goods) and the class of the subject’s attitude to the object (acquisition, possession, alienation). The
selective analysis of the institute of ownership is conducted on the basis of the developed function matrix. A
comprehensive review of the three classes of factors of owners’ attitude to property creates a complete picture of
the functions of the ownership institute, including all types of these relationships, rather than their separate
items. This system of ideas concerning the content of the subject area allows expanding the variety of the most
effective application of this tool in the social and economic relations and deepening the legal basis of the system
of economic relations.